When is the optimum time for the initiation of early rehabilitative exercise on the postoperative functional recovery of peri-ankle fractures? A network meta-analysis - Zhao, Ke; Dong, Shilei; Wang, Wei (Frontiers in Surgery, 2022)
Abstract Objective: The purpose of this study was to explore the safe and most effective initiation time for the functional recovery of patients with peri-ankle fractures after surgery. Method: We searched electronic databases, including the Cochrane Library, Embase, PubMed and the reference lists of relevant articles published from inception to October 30th, 2021. Two researchers independently performed literature screening and data extraction and evaluated the quality of the included literature using the Newcastle–Ottawa Scale. Network meta-analysis, including consistency testing, publication bias, and graphical plotting, was performed using Stata (v16.0). Results: A total of 25 articles involving 1756 patients were included in this study. The results of the meta-analysis showed that functional exercise within 2 days after surgery may result in lower VAS scores compared to other techniques (P < 0.05). Functional exercise within 12 months may lead to higher AOFAS scores than that of other techniques (P < 0.05). The total postoperative complication rate, including deep vein thrombosis, showed no statistically significant differences between any two interventions (P > 0.05). The results of the surface under the cumulative ranking (SUCRA) showed that functional exercise within two days postoperatively may have the lowest VAS scores (SUCRA = 82.8%), functional exercise within 1 week postoperatively may have the lowest deep vein thrombosis rate (SUCRA = 66.8%), functional exercise within 10 days postoperatively may have the fewest total postoperative complication rate (SUCRA = 73.3%) and functional exercise within 12 months postoperatively may contribute to the highest AOFAS scores (SUCRA = 85.5%). Conclusion: The results of this study suggest that initiation of rehabilitation within two days after surgery may be the best time to reduce postoperative pain; rehabilitation interventions within 10 days after surgery may be the optimal time for reducing the total postoperative complication rate, including deep vein thrombosis; and continued functional exercise within 12 months after surgery may steadily and ideally improve the function of the ankle joint. Keywords: Periarticular fractures, Rehabilitative exercise, Meta-analysis